Further refinement of the La Crosse County Vector Control Electronic Toolkit based upon partner feedback in a Western Wisconsin service region - Berg, Adam F. (My University, 2014)
This project involved the further refinement of the La Crosse County Vector Control Electronic Toolkit by using needs and capacity assessments with the regional public partners. The author assessed the needs and capacity of the counties served by the LCHD regarding their awareness of vector-borne (mosquito and tick-borne) disease and control, and their receptivity to the services already provided by the LCHD. It was the desire of Dave Geske, Vector Control Manager, to utilize the findings from this assessment to better inform and educate the population he serves regarding vector-borne disease and control. Prior to this project, the LCHD developed a Vector Control Electronic Toolkit, to provide an informational and educational resource to the counties they serve. As a result of this project, the LCHD was able to determine the needs of the counties they serve, along with the capacity to which public health representatives from partner agencies were able to achieve their vector control goals. The evaluation of the toolkit resulted in recommendations for its refinement as an informational and educational resource, as well as immediate additions strengthening its educational value.
Keywords: Parasitic insects--Wisconsin; Health risk assessment--Wisconsin; Public health--Wisconsin